2018
DOI: 10.1111/etap.12280
|View full text |Cite
|
Sign up to set email alerts
|

WITHDRAWN–Administrative Duplicate Publication—International Entrepreneurship: A Meta–Analysis on the Internationalization and Performance Relationship

Abstract: Kiss, A. N., Fernhaber, S., & McDougall–Covin, P. P. (2018). Slack, Innovation, and Export Intensity: Implications for Small– and Medium–Sized Enterprises. Entrepreneurship Theory and Practice. Jiang, H., Cannella, A. A., & Jiao, J. (2018). Does Desperation Breed Deceiver? A Behavioral Model of New Venture Opportunism. Entrepreneurship Theory and Practice. Hechavarría, D. M., Terjesen, S. A., Stenholm, P., Brännback, M., & Lång, S. (2018). More than Word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 152 publications
0
25
0
Order By: Relevance
“…That said, there is scope to go further in terms of highlighting behavioural dimensions of networks -including how they are developed -in relation to their effects on different dimensions of speed. A recent meta-analysis of INV research notes the importance of networks, but also calls for further efforts to specify the nature of their role in a more nuanced manner (Schwens et al, 2018). We turn to effectuation theory to identify a distinction between approaches to network-building that is germane to new ventures.…”
Section: Network-building and New Venture Internationalizationmentioning
confidence: 97%
“…That said, there is scope to go further in terms of highlighting behavioural dimensions of networks -including how they are developed -in relation to their effects on different dimensions of speed. A recent meta-analysis of INV research notes the importance of networks, but also calls for further efforts to specify the nature of their role in a more nuanced manner (Schwens et al, 2018). We turn to effectuation theory to identify a distinction between approaches to network-building that is germane to new ventures.…”
Section: Network-building and New Venture Internationalizationmentioning
confidence: 97%
“…However, it may well be that the rising costs of internationalization exceed the initial benefits: costs attributable to managerial and resource constraints arise because the need for coordination and communication increases as DOI increases (Qian 2002). Although it is suggested that SMEs could benefit more from increased DOI than large companies (Loth and Parks 2002), there is some evidence of a negative effect of foreign-market expansion on SME profitability Beamish 2001, 2006), although other scholars have found a positive relationship (Qian and Li 2003;Zhou et al 2007;Kuivalainen et al 2007;Schwens et al 2017). Finally, suggest that the nature of this relationship may depend on the characteristics of the company.…”
Section: The Impact Of Internationalization and Service Innovation Onmentioning
confidence: 99%
“…As today's business environment is changing rapidly, corporate innovations are more important than ever for business expansion and internationalization, particularly for SMEs (Schwens, Zapkau, Bierwerth, Isidor, Knight, & Kabst., 2018). SMEs willing to expand and perform in foreign markets very much need to focus on innovation (Li & Atuahene-Gima, 2001), which requires a positive attitude toward seeking new opportunities and the desire to take risks (see for instance Boling, Pieper, & Covin, 2016), characteristics that are associated with the early years of CEOs' careers (younger-tenure CEOs).…”
Section: Ceo Tenurementioning
confidence: 99%